NSDAP und Antisemitismus 1919-1933 - Michael Mayer (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2002)
– As there are apparently no doubts concerning the existence of Nazi anti-Semitism before 1933 regarding this topic - having largely been ignored by scholars of contemporary history - seems to be no use. This article tends to trace the role of anti-Semitism during the ascend of the Nazi-movement. Therefore, the author describes the theoretic function of this phenomena for the NSDAP by referring to Hitler's Weltanschauung and the official program of the party. But how did this anti-Jewish ideology find its way into the party's day-to-day agitation? By analysing Hitler's political speeches it is shown how, after 1925/26, the Führer tried to present himself as a moderate politician - for he had realised that the NSDAP had to become a mass-movement in order to gain political power in Weimar Germany. Vis-à-vis the party's antisemitic membership, mainly retailers and graduates, anti-Jewish stereotypes were pushed in propaganda. Yet, National Socialist anti-Semitism was not only opportunist in that it was played up or down depending upon when and where it hit responsive chords, it was also subject to the regional Gauleiter if this phenomena was promoted like in Streicher's Franconia or restricted like in Württemberg, Hamburg or Danzig. Only after the world-wide economic crisis of 1929 the NSDAP had considerable success in the Reichstag's elections. The party presented itself as the only power being capable to establish a new order in Germany. The propaganda focused on the main enemies of the National Socialists: Communism and the liberal democracy - in this context, the anti-Semitism was negligible.
urn:nbn:de:bvb:19-epub-9-4
Keywords: N44; 330